Social–ecological management results in sustained recovery of an imperiled salmon population. Issue 5 (12th May 2021) - Cote, D.; Van Leeuwen, T. E.; Bath, A. J.; Gonzales, E. K.; Cote, A.L.
Abstract : When faced with the loss of a population, resource managers often feel compelled to choose restoration strategies perceived to have low risk, such as the management of the ecological components of the system or the application of regulatory measures. It can be counterintuitive to share decision‐making and resource management with those who want to harvest an imperiled population, yet this social–ecological strategy resulted in the recovery of a wild Atlantic salmon population in Newfoundland, Canada. Atlantic salmon supported widespread commercial, subsistence, and recreational fisheries but declines in abundance necessitated closures and other conservation strategies across many areas of Atlantic Canada in the 1990s. Recreational angling for Atlantic salmon was closed in Terra Nova National Park's Northwest River in 1995 when counts were below expectations based on available habitat. The population continued to decline, even though commercial and recreational fishing mortality had been eliminated, and by 2001, extirpation seemed imminent. Despite pressure to pursue conventional strategies such as catch and release fishing and stocking, public consultation and human dimensions research revealed that illegal fishing was likely contributing to declines and that distrust of resource managers created an environment conducive to poaching. Disrupting this dynamic could not be achieved with conventional strategies, so instead an adaptive management approach was implemented that incorporated local collaboration and improved transparency, and was responsive to positive changes in behavior. Adoption of social–ecological management led to a rapid and sustained recovery of the salmon population in Northwest River, out‐performing populations in adjacent rivers managed with conventional management strategies.